PERANCANGAN SISTEM INFORMASI PEMBELIAN DAN PENJUALAN PADA PT.HOK TONG JAMBI MENGGUNAKAN MICROSOFT VISUAL BASIC - Laura Prasasti; Ronald Naibaho; Chintia Aprilia (LPPM Universitas Adiwangsa Jambi, 2022)
This study originated from the problems that occur in the data processing system purchases and sales that are running, namely: if required information quickly, then the search takes a long time, frequent errors in inputting data purchases and sales as well as the slow creation of reports that must be given to the head office. This study aims to to design information systems purchase and sales at PT. Hok Tong Jambi uses Visual Basic 2019 so that it can be a solution to the problems that occur. The research method applied in this study is the development of waterfall method. The design of this research is started from Log in Input design, main Menu design, purchase Data Design, purchase Input design, purchase price Input Design, Sales Data Design, Sales Input design, demand data Input design, outgoing goods demand Input design,sales table Input design, purchase and sales report Filter Input design. Based on the discussion and the results of Information Systems Design purchase and sale at PT.HOK TONG JAMBI that has been done, it can be concluded that through the use of Microsoft Visual Basic simplify the process of searching and processing data purchase and sale transactions. With this purchase and sales information system, the purchase and sales transaction process can produce purchase and sales transaction reports.